Analisis Pelaksanaan Rekonsiliasi Fiskal Atas Laporan Keuangan Komersial PT. XYZ Untuk Menghitung PPh Badan Terutang - M. Anjar Nurulhayat (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2023)
This research was conducted to determine whether implementation of fiscal reconciliation of commercial financial statements that had been carried out by PT. XYZ in accordance with applicable tax regulations and to find out the amount of tax payable based on applicable tax regulations. This study uses a qualitative method. Results showed that implementation of fiscal reconciliation of commercial financial statements made by PT. XYZ are not in accordance with applicable tax regulations. Calculation of Corporate Income Tax Payable carried out by the company is Rp.253.437.345, while the calculation of Corporate Income Tax Payable by the Author based on applicable tax regulations, decreases to Rp.211.945.161, there is a difference in Corporate Income Tax Payable of Rp.41.492.184 , the difference occurs because there are errors in costs that must be corrected by fiscal.